2018
DOI: 10.1111/cei.13084
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-independent pathways underlie the pathogenesis of murine cytomegalovirus-associated secondary haemophagocytic lymphohistiocytosis

Abstract: Haemophagocytic lymphohistiocytosis (HLH) constitutes a spectrum of immunological disorders characterized by uncontrolled immune activation and key symptoms such as fever, splenomegaly, pancytopenia, haemophagocytosis, hyperferritinaemia and hepatitis. In genetic or primary HLH, hyperactivated CD8 T cells are the main drivers of pathology. However, in acquired secondary HLH, the role of lymphocytes remains vague. In the present study the involvement of lymphocytes in the pathogenesis of a cytomegalovirus-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
(170 reference statements)
0
1
0
Order By: Relevance
“…HLH diagnoses in the absence of obvious genetic lesions in known FHLH genes are defined by a set of clinical criteria, leaving scope for many causative triggers and pathologic effectors (9). Despite the precedence that HLH disease pathogenesis is dependent on IFNγ, several murine models have shown that HLH disease can be driven by alternative cytokines (10,11). Additionally, a number of patients have developed HLH-like or macrophage activation syndrome (MAS)-like disease in the setting of mutations in the IFNγ receptor (IFNγR), rendering them unresponsive to IFNγ (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…HLH diagnoses in the absence of obvious genetic lesions in known FHLH genes are defined by a set of clinical criteria, leaving scope for many causative triggers and pathologic effectors (9). Despite the precedence that HLH disease pathogenesis is dependent on IFNγ, several murine models have shown that HLH disease can be driven by alternative cytokines (10,11). Additionally, a number of patients have developed HLH-like or macrophage activation syndrome (MAS)-like disease in the setting of mutations in the IFNγ receptor (IFNγR), rendering them unresponsive to IFNγ (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%